Organizar la contabilidad en la empresa comercial “Minimarket Steven” de la Sra Heidi Margorie Arpi Morocho, de la parroquia Tundayme, periodo del 01 de abril al 30 de junio del 2023. - Sanchez Zhungo, Rashel Nicolle (2024)
This Curricular Integration Work entitled Organizing the accounting in the commercial company "Minimarket Steven" of Mrs Heidi Margorie Arpi Morocho, of the parish Tundayme, the period from April 1 to June 30, 2023, is intended to propose an accounting organization that will support its owner for the knowledge of the real economic-financial situation of the business, and thus make the improvement decisions. We began by developing the plan and manual of accounts according to the needs and nature of the business, where each account of the assets, liabilities, equity, income, costs and expenses was ordered and codified, making known their concepts and the respective debits and credits of each account, later, for didactic purposes and due to the large number of existing products, the multiple account inventory control system was applied to control the merchandise. Next, the initial inventory was elaborated by physically verifying the values, assets and liabilities of the business, determining that the merchandise inventory account has a more representative value since the company is engaged in the purchase and sale of merchandise. Subsequently, the Initial Statement of Financial Position was realized, detailing the assets, liabilities and equity accounts. With the information provided by the owner of the company, it was possible to start the main records beginning with the journal, general ledger, trial balance, in addition to the auxiliary sales, purchases, accounts receivable, and accounts payable, which facilitated and simplified the recording of the commercial transactions, resulting in the Financial Statements which reflect the economic-financial situation of the business, the Income Statement, Statement of Financial Position, Statement of Cash Flow and the Explanatory Notes, finally the respective conclusions and recommendations were presented. The elaboration of this work, both in its theoretical and practical part, is developed using different methods, starting with the scientific method that served for the classification of concepts, followed by the deductive and inductive method that allowed to order and classify the information gathered and to carry out the accounting process, the mathematical method was used for the development of the operations that helped to obtain the Financial Statements and finally the analytical and synthetic methods were used to analyze and give solutions to the problems that were found in the respective operations, facilitating the realizing of the conclusions and recommendations that are expected to be of help for a correct decision making.